Rape among the Shona in Zimbabwe - Charamba, Tyanai (Nova Science Publishers, 2016)
This chapter has three goals. Firstly, it proposes that certain traditional Shona maniage procedures, customs and practices are among the major factors that promote illegal sexual encounters of which rape is part. Secondly, it examines the efforts made by different governments in the history of Zimbabwe to curb those customs. Thirdly, it exposes circumstances that continue to sustain those marriage customs that perpetuate unlawful sexual conduct.